'Road map' of the development of the technological component of the strategy of national security. Issue 1 (2nd January 2017) - Sigov, A. S.; Bukharin, S. N.; Epishin, K. V.; Yushkov, E. S.
Abstract: This article is devoted to the development of guidelines for road mapping in planning the development of the technological component of structures of national security. Making the 'road map' is reduced to the method of conventional optimization i.e. achievement of the target in conditions of severe limitations of existing resources taking into account the effect of controlled and uncontrolled factors. Such a result can be regarded as a scientific novelty.